2016
DOI: 10.1210/en.2015-2082
|View full text |Cite
|
Sign up to set email alerts
|

Paraventricular NUCB2/Nesfatin-1 Supports Oxytocin and Vasopressin Neurons to Control Feeding Behavior and Fluid Balance in Male Mice

Abstract: Nesfatin-1, derived from nucleobindin-2 (NUCB2), is expressed in the hypothalamus, including the paraventricular nucleus (PVN), an integrative center for energy homeostasis. However, precise role of the NUCB2/nesfatin-1 in PVN remains less defined. The present study aimed to clarify physiological and/or pathophysiological roles of endogenous NUCB2/nesfatin-1 in PVN by using adeno-associated virus vectors encoding short hairpin RNAs targeting NUCB2 in mice. PVN-specific NUCB2 knockdown primarily increased food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 34 publications
3
36
0
1
Order By: Relevance
“…In this study, the prominent immunoexpression of NUCB2/nesfatin-1 in the PVN, SON, IFN, and LHA is in agreement with neuroanatomical evidence and functional analyses from animal studies, revealing that NUCB2/nesfatin-1 effects on energy homeostasis are primarily mediated by PVN, SON, Arc (IFN), and LHA NUCB2/nesfatin-1 [3, 5-10, 21, 29-31, 33, 42-44]. NUCB2/nesfatin-1 localization pattern in human hypothalamic nuclei is indicative of a potential function for NUCB2/nesfatin-1 as an integral regulator of energy homeostasis; moreover, it could imply a role for NUCB2/nesfatin-1 in the regulation of other neuroendocrine and autonomic functions, which will require further studies in humans.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the prominent immunoexpression of NUCB2/nesfatin-1 in the PVN, SON, IFN, and LHA is in agreement with neuroanatomical evidence and functional analyses from animal studies, revealing that NUCB2/nesfatin-1 effects on energy homeostasis are primarily mediated by PVN, SON, Arc (IFN), and LHA NUCB2/nesfatin-1 [3, 5-10, 21, 29-31, 33, 42-44]. NUCB2/nesfatin-1 localization pattern in human hypothalamic nuclei is indicative of a potential function for NUCB2/nesfatin-1 as an integral regulator of energy homeostasis; moreover, it could imply a role for NUCB2/nesfatin-1 in the regulation of other neuroendocrine and autonomic functions, which will require further studies in humans.…”
Section: Discussionsupporting
confidence: 88%
“…It has been shown that the NUCB2/Nesf-1 expression in PVN exhibits circadian rhythm featured with a rise in light period (LP) in rodents41, and that it serves to produce circadian feeding rhythm and to restrict LP food intake3841. Moreover, in both obese rodent models and PVN NUCB2 knockdown mice, the loss of circadian rhythm of PVN NUCB2/Nesf-1 expression leads to impaired circadian feeding rhythm and hyperphagia3841, both of which trigger obesity and metabolic syndrome. Hence, the present results suggest a novel strategy to treat obesity: supplementation of FGF21 could restore endogenous PVN NUCB2/Nesf-1 expression and thereby reconstruct circadian feeding rhythm to ameliorate obesity and metabolic syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the functional relevance of the interaction between FGF21 and PVN neurons particularly in feeding regulation remains unknown. Cumulative evidence has indicated that NUCB2/Nesf-1 neurons in PVN play a role in suppressing feeding3435363738, reducing body weight3539, and increasing energy expenditure in rodents40. We reported that the NUCB2/Nesf-1 located in PVN regulates both total amount and circadian rhythm of food intake in rodents343841.…”
mentioning
confidence: 87%
“…application of nesfatin-1 increased dry heat loss of rats over eight hours to 8.49 ± 1.09 W/kg 0.75 compared to 7.09 ± 0.84 W/kg 0.75 in control animals (Wernecke et al 2014). Thereby other structures than the PVN are involved because NUCB2 knockdown in this nucleus does not affect energy expenditure (Nakata et al 2016).…”
Section: Thermogenesismentioning
confidence: 91%